FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE DENGAN PERTUMBUHAN PERUSAHAAN SEBAGAI VARIABEL INTERVENING - Bahtiar Effendi (Universitas Multimedia Nusantara, 2022)
Abstract - Firm value is one of the measurements used to gain investor and creditor confidence. A high company value will make investors believe in investing their capital or investing in a company, because a high company value indicates good company performance and is a measure of the high level of shareholder prosperity indirectly. This study aims to determine whether there is an influence between earnings per share (EPS), capital structure, and dividend policy on firm value with company growth as an intervening variable. The companies studied are consumer goods companies listed on the Indonesia Stock Exchange in 2018 – 2021. This research is a quantitative study. The population in this study were consumer goods companies and the sample method used was purposive sampling. The data analysis technique used is descriptive statistics, multiple linear regression analysis, coefficient of determination (R2), partial test (t test) and simultaneous test using SPSS version 26.00. The results of the study found that earnings per share has a significant effect on firm value, dividend policy has a significant effect on firm value, capital structure has no effect on firm value, firm growth has no effect on firm value, and firm growth has no effect as an intervening variable. in influencing earnings per share, dividend policy, and capital structure on firm value. Keywords: Firm Value; Earning Per Share; Capital Structure; Dividend Policy; Company Growth